2012
DOI: 10.1074/jbc.m111.333245
|View full text |Cite
|
Sign up to set email alerts
|

A Rab8 Guanine Nucleotide Exchange Factor-Effector Interaction Network Regulates Primary Ciliogenesis

Abstract: Background: Exocytosis at the plasma membrane mediated by Rabin8 is essential for primary ciliogenesis. Results: Rabin8 activation involves the relief of its autoinhibition. Rabin8 interacts with the exocyst component Sec15 upon its activation. Conclusion: The Rab8 guanine nucleotide exchange factor-effector interaction is important for exocytosis and primary ciliogenesis. Significance: The study sheds light on our understanding of the regulation of exocytosis and ciliogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
132
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 45 publications
6
132
0
1
Order By: Relevance
“…For the GDP release assay in vitro, we first incubated Rabin8 with ERK2-CA in the presence of ATP for 30 min for phosphorylation. Rab8a was preloaded with [ 3 H]GDP, and the amount of bound [ 3 H]GDP was monitored at various time points as previously described (16,18). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the GDP release assay in vitro, we first incubated Rabin8 with ERK2-CA in the presence of ATP for 30 min for phosphorylation. Rab8a was preloaded with [ 3 H]GDP, and the amount of bound [ 3 H]GDP was monitored at various time points as previously described (16,18). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that a Rabin8 mutant ("Rabin8Δ(300-305)") lacking a highly conserved region (amino acid 300-305 "SLYNEF") after the GEF domain displayed higher binding affinity for Rab8 and showed stronger GEF activity than wild-type Rabin8 (18). It is possible that Rabin8 adopts an autoinhibitory conformation, with its C terminus masking the GEF catalytic domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Thereafter, activated Rab8 in coordination with the exocyst complex, enables polarized traffic of vesicles derived from the TGN or RE to the base of the PC. 55 Under serum-starvation conditions, primary dermal fibroblast cells derived from LS patients or cell lines (RPE-1 and NIH3T3) in which Ocrl1 was knocked-down (KD) failed to develop a functional PC. 38 In addition to defective ciliogenesis, Ocrl1-KD cells also showed deficiencies in localization of ciliary receptors to the short abnormal PCs that some LS cells develop.…”
Section: Rhogap Domain-containing Protein Ocrl1 Regulates Polarized Mmentioning
confidence: 99%
“…Il est cependant tentant d'imaginer un rôle de l'exocyste, machinerie permettant l'ancrage et la fusion des vésicules d'exocytose avec la membrane plasmique. Certaines sous-unités de l'exocyste sont en effet requises pour la ciliogenèse (SEC10, SEC15) [27,28]. De plus, dans les cellules multiciliées de l'épiderme de l'embryon de xénope, l'association des corps basaux à des vésicules exprimant SEC8 est requise pour leur ancrage à la membrane apicale [7].…”
Section: Les Appendices Distauxunclassified